Peran Orang Tua Dalam Mengatasi Stres Sekolah Online Melalui Keterampilan Psychological First Aid (PFA) - Rusdi Kasman; Nuha Lutfiah; Hadining; Hafsah Nur Afifah; Hikmah Khamelia; Hanisa (Prophetic guidance and counseling journal, 2022)
The situation of the Corona Virus Disease 2019 pandemic or Covid-19 which is endemic throughout the world, including Indonesia.These conditions have changed every field of human life, one of which is the field of education. The government then determined that the learning process was carried out at home through online or distance learning to provide a meaningful learning experience for students. Online learning has an impact on students, both positively and negatively. One of the negative impacts is psychological pressure. The written idea submitted is an idea related to efforts to deal with online school stress faced by students during the COVID-19 pandemic. The alleviation of the problem in question is through the Psychological First Aid skill approach. Ways to realize PFA activities include, preparing the PFA concept to deal with online school stress by students. Next, ideas are submitted to the education and culture office to be known and provide legality. Socialization of PFA ideas to schools at every level of education. Abstrak         Situasi pandemi Corona Virus Disease 2019 atau dikenal Covid-19 yang mewabah seluruh dunia termasuk Indonesia. Kondisi tersebut telah merubah setiap bidang kehidupan manusia, salah satunya adalah bidang pendidikan. Pemerintah kemudian menetapkan proses belajar dilaksanakan di rumah melalui pembelajaran daring (Online) atau jarak jauh dilaksanakan untuk memberikan pengalaman belajar yang bermakna bagi siswa. Pembelajaran daring memiliki dampak kepada peserta didik, baik secara positif maupun negatif. Salah satu dampak negatif adalah tekanan psikologis. Gagasan tertulis yang diajukan adalah gagasan terkait upaya penanganan stres sekolah Online yang dihadapi peserta didik selama masa pandemi covid-19. Pengentasan permasalahan yang dimaksud melalui pendekatan keterampilan Psychological First Aid. Cara merealisasikan kegiatan PFA meliputi, Penyusunan konsep PFA untuk mengatasi stres sekolah Online oleh mahasiswa Selanjutnya, gagasan diajukan ke dinas pendidikan dan kebudayaan untuk diketahui serta memberikan legalitas Sosialisasi gagasan PFA ke sekolah di setiap jenjang pendidikan.